Frailty and Incident Depressive Symptoms During Short- and Long-Term Follow-Up Period in the Middle-Aged and Elderly: Findings From the Chinese Nationwide Cohort Study - Liu, Haiyang; Yang, Xu; Guo, Lei-lei; Li, Jin-long; Xu, Guang; Lei, Yunxiao; Li, Xiaoping; Sun, Lu; Yang, Liu; Yuan, Ting; Wang, Congzhi; Zhang, Dongmei; et al. (Frontiers in Psychiatry, 2022)
Objective: Prefrailty and frailty are two common conditions among older individuals. Recent studies have reported the association between frailty and depressive symptoms, but whether those conditions could predict depressive symptoms is still inconsistent in a few longitudinal studies. In our study, we aimed to estimate the cross-sectional and longitudinal associations between frailty and incident depressive symptoms in a nationally representative sample of community-dwelling middle-aged and older Chinese adults. Method: Data were obtained from the CHARLS. We excluded participants with no follow-up data. The numbers of individuals who completed the baseline surveys were 2579 and follow-up surveys were 839 for the short-term and 788 for the long-term. In addition, Frailty was measured by the Fried criteria and depressive symptoms were estimated by the CES-D. Logistic regression was used to analyze the OR, and 95% CI for the cross-sectional associations of frailty and its components with depressive symptoms in the participants at baseline. Cox proportional hazards analysis was conducted using the HR, and 95% CI for the prospective associations of baseline frailty and pre-frailty and its component in the participants without depressive symptoms at baseline. Results: At baseline, 57.93% of participants had depressive symptoms and 55.84% had pre-frail and 11.63% had frailty. In the cross-sectional analysis, both pre-frailty and frailty were associated with depressive symptoms. In the longitudinal analysis, frailty and pre-frailty were not significantly associated with incident depressive symptoms in a full-adjusted model among participants free of baseline depressive symptoms during the short-term. However, frailty and pre-frailty were significantly associated with incident depressive symptoms during the short term. In the components of frailty, slowness was associated with an increased risk of depressive symptoms onset during the short-term. Weakness and exhaustion were associated with increased risk of depressive symptoms onset during the short-term. Conclusion: Among the middle-aged and older adults, frailty, pre-frailty did not predict depressive symptoms during 2 years of follow-up, when accounting for the potential confounders, slowness considered alone predicted depressive symptoms. Additionally, frailty, pre-frailty predicted depressive symptoms during 4 years of follow-up, when accounting for the potential confounders, weakness and exhaustion considered alone predicted depressive symptoms.